FIIs and Indian Stock Market: A Causality Investigation; Zagraniczni inwestorzy instytucjonalni i rynek akcji w Indiach: badania zwiazku przyczynowego - Minakshi Paliwal; S. D. Vashishtha (Comparative Economic Research. Central and Eastern Europe, 2011)
While the volatility associated with portfolio capital flows is well known, there is also a concern that foreign institutional investors might introduce distortions in the host country markets due to the pressure on them to secure capital gains. In this context, present chapter attempts to find out the direction of causality between foreign institutional investors (FIIs) and performance of Indian stock market. To facilitate a better understanding of the causal linkage between FII flows and contemporaneous stock market returns (BSE National Index), a period of nineteen consecutive financial years ranging from January 1992 to December 2010 is selected. Granger Causality Test has been applied to test the direction of causality. – – Aczkolwiek brak stabilnosći zwiazany z przepływami kapitału portfelowego jest dobrze znany, to istnieje roẃniezȯbawa, zė zagraniczni inwestorzy instytucjonalni moga wprowadzacźakłoćenia na rynkach krajoẃ przyjmujacych z uwagi na wywierana na nich presje, aby zapewniacźyski kapitałowe. W tym konteksćie niniejszy rozdział prob́uje poznacḱierunek przyczynowosći pomiedzy zagranicznymi inwestorami instytucjonalnymi (FIIs) i działaniem indyjskiej giełdy. Aby ułatwicĺepsze zrozumienie zwiazku przyczynowego miedzy przepływami FII i majacymi miejsce w tym samym czasie wynikami giełdy papieroẃ wartosćiowych (BSE National Index), wybrany został okres dziewietnastu kolejnych lat poczawszy od stycznia 1992 do grudnia 2010. Do zbadania kierunku przyczynowosći zastosowano test przyczynowosći Grangera.
Keywords: 330